1998
DOI: 10.1021/la971187j
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Films of p-tert-Butylcalix[8]arene. Conformations at the Water−Air Interface and Complexation of Fullerene C60

Abstract: Langmuir monolayers of p-tert-butylcalix[8]arene (CAL8) at the water−air interface were studied as a function of temperature (between 288 and 308 K), of the spreading solvent (benzene, toluene, dichloromethane, chloroform, and carbon tetrachloride), and in a mixture with fullerene C60. Two different mixed systems were studied:  (i) spreading isotherms (surface pressure versus molecular area) after separated spreading of CAL8 and C60 solutions (1/1 molar ratio) and (ii) spreading isotherms of the C60−CAL8 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
5
40
0
Order By: Relevance
“…This maximum head-group area is reflected in the transition observed for 3, 6, 8, and 9 at 130 2 ( Figure 1). The higher collapse pressures observed for pyrogallol [4]arenes bearing hexyl (6), nonyl (8), and dodecyl (9) side chains than for pyrogallol [4]arene 3 with a propyl side chain results from stronger van der Waals interactions of the longer alkyl chains. It is notable that the collapse pressures for 6, 8, and 9 are the same.…”
Section: Pyrogallol[4]arenes Having Straight (Normal) Alkyl Chainsmentioning
confidence: 93%
See 2 more Smart Citations
“…This maximum head-group area is reflected in the transition observed for 3, 6, 8, and 9 at 130 2 ( Figure 1). The higher collapse pressures observed for pyrogallol [4]arenes bearing hexyl (6), nonyl (8), and dodecyl (9) side chains than for pyrogallol [4]arene 3 with a propyl side chain results from stronger van der Waals interactions of the longer alkyl chains. It is notable that the collapse pressures for 6, 8, and 9 are the same.…”
Section: Pyrogallol[4]arenes Having Straight (Normal) Alkyl Chainsmentioning
confidence: 93%
“…In a few cases, the side chains are functionalized, for example by a terminal halogen atoms. [8] A goal to prepare previously unstudied Pgs with branched side chains and to exploit interchain interactions that might augment or alter the organizational tendencies of the Pg head groups, was strongly encouraged by the results described above. Thus, compounds 4, 5, and 7, which have 2-propyl, 3-pentyl, and 4-heptyl side chains, respectively, were prepared, characterized, and studied.…”
Section: Pyrogallol[4]arenes Having Straight (Normal) Alkyl Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, the characterization absorptions are 279, 291 nm and 303, 345 nm for calix [4]arene and Cu(SBC 18 ) 2 , respectively. However, the bands of mixture with 1 : 1 Cu(SBC 18 ) 2 : calix [4]arene are not the simple adduct of the two components' absorptions and some degree of shift can be observed, indicating that interaction arising from headgroups truly exists in mixed LB films (25), which can be explained by the molecular arrangement shown in Fig. 6.…”
Section: Lb Filmsmentioning
confidence: 95%
“…Since calixarenes as the frequently used host compounds were introduced into the interface science at the end of 1980s, [1][2][3][4][5][6][7] Langmuir monolayers and Langmuir-Blodgett (LB) films of calixarenes have shown interesting properties and promising prospect. [8][9][10][11][12][13] Besides calixarene with long alkyl chains, [14][15][16] Shinkai has demonstrated that lower rim calix [4]arene esters without long alkyl chains can also form stable monolayers at the air/water interface, and the monolayers are able to recognize alkali cations.…”
Section: Introductionmentioning
confidence: 99%